TINJAUAN HUKUM PIDANA TERHADAP PELANGGARAN PEMILU 2019 DI KABUPATEN KENDAL - adminjfh, adminjfh; Mila, Yusrina Handayani S.H.; Mila, Saiful Amar (Journal Legal Dialectics, 2022)
The general election is a democratic party for the people to be able to use their constitutional rights in politics, both to be elected and to vote, as well as in holding the 2019 general election which was held simultaneously in various regencies and provinces that followed it, especially in Kendal district where it was suspected that there were problems that had to be resolved. So this study the author takes the title Review of Criminal Law Against Election Violations 2019 at the Kendal Bawaslu.This study aims to find out how the form of criminal acts against 2019 election violations in Kendal Regency and how the role of the Bawaslu off Kendal in efforts to resolve 2019 election violations in Kendal Regency.The research method used is qualitative research with sociological juridical. This study uses two sources of data, namely primary data in the form of data from interviews on the object under study and secondary data related to research.From the results of an interview with one of the Bawaslu off Kendal commissioner staff, Mr. Abdul Latif, S.H, that there was a violation in the 2019 election at TPS 02 Balok Village, Kendal District. There were 3 voters from outside the region, in this case from Brebes Regency and not registered in the DPT or DPTb who exercised their right to vote in Kendal Regency at TPS 02 Balok Village, Kendal District, but did not bring the A5 form so that Bawaslu recommended to the Kendal Regency KPU to a re-voting is conducted. In resolving administrative violations at TPS 02 Balok Sub-district, Kendal District, Bawaslu issued a letter Number 325/BawasluProv.JT.13/PM.05.02/IV/2019 concerning the Recommendation for Re-voting (PSU) on 20 April 2019 and a warning letter regarding the procedural issuance of A5 with Number 367/Bawaslu Prov JT.13/PM.05.02/V/2019 regarding a written warning to the Kendal KPU on May 6, 2019.